Analysis of the Influence of Service Quality, Price Perception, Location, and Promotion on the Decision to Purchase a Toyota Avanza Car: (Case Study at PT Nasmoco Wonosobo) - Anggun Setiawan; Bahtiar Efendi; Agus Yudianto (Journal of Economics, Management, and Business, 2025)
Objective - The purpose of this study is to determine the impact of benefit quality, cost recognition, administration, and progress on purchasing choices. Method - The population in this study were all consumers who bought and used Toyota Avanza cars (Study at PT. Nasmoco Wonosobo). The sample of this study was some consumers who bought and used Toyota Avanza cars, while the sampling technique used was total sampling, namely the entire population was used as a sample. The sample in this study amounted to 96 respondents. The data collection method for this study was interviews, questionnaires, and literature studies and data analysis methods using multiple linear regression, and data that had met the requirements were instrument testing, Classical Assumption testing, and Goodness of Fit of a Model that had been processed using the SPSS program (Statistical Package for Social Science). Result - This study shows that the variables of service quality, price perception, location and promotion have a positive and significant effect on purchasing decisions. Based on the coefficient determinant value, it is known that the three independent variables used can influence consumers in making purchasing decisions by 82.2% while the remaining 17.8% is influenced by other variables not explained in this study.